2021
DOI: 10.1364/boe.417896
|View full text |Cite
|
Sign up to set email alerts
|

Clinical integration of fast Raman spectroscopy for Mohs micrographic surgery of basal cell carcinoma

Abstract: We present the first clinical integration of a prototype device based on integrated auto-fluorescence imaging and Raman spectroscopy (Fast Raman device) for intra-operative assessment of surgical margins during Mohs micrographic surgery of basal cell carcinoma (BCC). Fresh skin specimens from 112 patients were used to optimise the tissue pre-processing and the Fast Raman algorithms to enable an analysis of complete Mohs layers within 30 minutes. The optimisation allowed >95% of the resection surface area to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The combination of other imaging modalities with selective sampling of suspicious areas by RS as a powerful labelfree analytical technique has also been explored [128,129]. Such approaches include MRI, second harmonic generation, OCT, AFI, total internal reflection fluorescence, or quantitative phase microscopy [130][131][132][133][134][135][136][137][138]. In general, the basic concept behind these multimodal approaches is to combine the high sensitivity of an imaging modality (i.e.…”
Section: Intraoperative Use Of Raman Spectroscopymentioning
confidence: 99%
“…The combination of other imaging modalities with selective sampling of suspicious areas by RS as a powerful labelfree analytical technique has also been explored [128,129]. Such approaches include MRI, second harmonic generation, OCT, AFI, total internal reflection fluorescence, or quantitative phase microscopy [130][131][132][133][134][135][136][137][138]. In general, the basic concept behind these multimodal approaches is to combine the high sensitivity of an imaging modality (i.e.…”
Section: Intraoperative Use Of Raman Spectroscopymentioning
confidence: 99%
“…The system had a sensitivity of 90% and a specificity of >32% for determining benignity [118]. Recently, RS was suggested to be a promising tool to assess surgical margins during Mohs micrographic surgery of BCC [119].…”
Section: Clinical Applications For Specific Skin Cancers Nmsc and Melanomamentioning
confidence: 99%
“…As an example, we selected BCC, which is the most common type of cancers in humans [32]. While Raman spectroscopy has been widely used for discrimination between normal tissue and cancer [2], including BCC [14,16], we are not aware of any reports using TG Raman spectroscopy. Previous studies showed that Raman spectra of BCC are characterised by higher signals assigned to nucleic acids and lower intensity bands of collagen compared to Raman spectra of dermis in normal skin [33].…”
Section: Discrimination Between Cancer and Normal Tissue Using Tg Ram...mentioning
confidence: 99%
“…Any further distribution of this work must maintain attribution to the author(s) and the title of the work, journal citation and DOI. and treatment: hand-held Raman probes for in-vivo cancer diagnosis [3,4], detection of residual tumour during cancer surgery [5], bone disease [6], Raman endoscopes [7][8][9], or ex-vivo Raman needle-probes [10][11][12] and multimodal Raman-autofluorescence (AF) [13][14][15] to assess completeness of tumour excision during cancer surgery. When acquiring Raman spectra of biological samples, it is important to block any stray or ambient light from reaching the detector as this background signal can swamp the tissue specific Raman bands.…”
Section: Introductionmentioning
confidence: 99%